The supramolecular self-assembly of 5-fluorouracil and caffeic acid through cocrystallization strategy opens up a new way for the development of synergistic antitumor pharmaceutical cocrystal. Issue 45 (7th November 2020) - Yu, Yue-Ming; Wang, Ling-Yang; Bu, Fan-Zhi; Wang, Lin-Lin; Li, Yan-Tuan; Wang, Cheng; Wu, Zhi-Yong
Abstract : Cocrystallizing with caffeic acid (CF) provides a new strategy for effectually optimizing in vivo /vitro properties of anticancer drug 5-fluorouracil (FL). Abstract : In order to give full play to the superiority of cocrystallization techniques to overcome biopharmaceutical limitations in vitro and ameliorate pharmacokinetic properties in vivo together with heightening the antitumor abilities of the anticancer drug 5-fluorouracil (FL), and to gain some further insights into the development of novel pharmaceutical cocrystals with synergetic antitumor activity between an active pharmaceutical ingredient and the former cocrystal, a new cocrystal of FL with caffeic acid (CF), namely FL-CF-2H2 O, has been successfully exploited and systematically studied. Single-crystal X-ray diffraction analysis confirms that the asymmetric unit of the newly synthesized cocrystal consists of one FL, one CF and two solvent water molecules, in which the two complementary FL and CF molecules compose a planar hydrogen-bonding pair. Water molecules fill in the hole surrounded by three arrays of the pairs and link each other via hydrogen bonds to form a three-dimensional supramolecular network, which is further reinforced by aromatic packing interactions. The cocrystal characteristics in vitro and in vivo are systematically evaluated through a combination of theoretical and experimental methods. It is found that the permeability and solubility of FL from the FL-CF-2H2 O cocrystal are synchronously enhanced relative to pure FL, which is supported by molecular electrostatic potential calculation and Hirshfeld surface analysis. Interestingly, the ameliorated in vitro biopharmaceutical characteristics can efficaciously change the in vivo optimized pharmacokinetics with prolonged half-life and increased bioavailability compared with FL itself. What is even more interesting is that CF and FL in the cocrystal exhibit synergistic antitumor effects on tested cell lines. Thus, this work not only provides a new crystalline form for FL with potential application prospects, but also initiates an intelligent idea for the development of synergistic antitumor pharmaceutical cocrystals.